2019
DOI: 10.1007/s12220-019-00239-7
|View full text |Cite
|
Sign up to set email alerts
|

Hermitian Curvature Flow on Compact Homogeneous Spaces

Abstract: We study a version of the Hermitian curvature flow on compact homogeneous complex manifolds. We prove that the solution has a finite exstinction time T > 0 and we analyze its behaviour when t → T . We also determine the invariant static metrics and we study the convergence of the normalized flow to one of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For other relevant results on the Anomaly flow, we refer the reader to [4,12,14,37,39]; while, for some results on the Hermitian curvature flow in the homogeneous setting we refer the reader to [3,10,28,36,35,42,43,46,50].…”
Section: Introductionmentioning
confidence: 99%
“…For other relevant results on the Anomaly flow, we refer the reader to [4,12,14,37,39]; while, for some results on the Hermitian curvature flow in the homogeneous setting we refer the reader to [3,10,28,36,35,42,43,46,50].…”
Section: Introductionmentioning
confidence: 99%
“…Several members of the HCF family are actively being studied in the homogeneous case. We refer the reader to [1,4,7,8,12,18,19,20,21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…In [22], Ustinovskiy studied the HCF + on complex homogeneous manifolds G/H. He showed that the space of (generically not G-invariant) metrics induced by left-invariant metrics on G is preserved, and that the flow in this case is governed by an ODE on the Lie algebra of G which is independent of the isotropy H. In [15], Panelli and Podestà studied the HCF + on compact homogeneous spaces. And the HCF + on 2-step nilpotent Lie groups was studied by Pujia in [18].…”
Section: Introductionmentioning
confidence: 99%